Highly antifouling field-effect transistor biosensors: From interface design to practical applications - Jiajun Tong; Rong Mu; Luming Zhi; Ruilian Yu; Kemin Wang; Zijun Zhao; Yiwei Liu; Taiping Qing; Xiaofeng Liu (Chemical Engineering Journal, 2026)

Stepwise hydrolysis reduces allergenicity of α-lactalbumin through epitope removal and structural modulation - Qing Zhao; Guangqing Mu; Ruida Ma; Qi Sun; Peng Sun; Xiaomeng Wu; Fanhua Kong (Food Research International, 2026)

Effects of fine particle migration caused by one wetting-drying cycle on desiccation micro-cracks in intact loess - Zhi-yuan He; Peng-hui Ma; Qing-yi Mu; Chao Zhou; Ke Mu; Zhi-jie Jia; Jian-bing Peng (Engineering Geology, 2026)

Frasnian-Famennian boundary successions (Upper Devonian) of different depositional settings and correlation in South China: Multiple stratigraphic approaches - Daizhao Chen; Zhenghui Guo; Liyu Zhang; Hairuo Qing; Lei Liang; Huihong Liao; Mu Liu; Maurice E. Tucker (Earth-Science Reviews, 2026)

Methanotrophs and co-occurring microbial taxa: Genomic potential for carbon, nitrogen, and sulfur cycles in newly formed high-altitude proglacial lakes - Meiqi Huang; Shengjie Li; Guangli Mu; Xiaodong Li; Qing Yang; Bo Shao; Qianggong Zhang; Yindong Tong (Environmental Research, 2026)

A Systematic Survey and Geoconservation Strategy for Geoheritage Resources in the Guang’an Region, Southwest China - Sibao Zhu; Hong-Xu Mu; Zizheng Wang; Qingwei Song; Minghui Li; Qing Zhou; Jun Liu; Bangguo Zhou; Canhai Jin (Geoheritage, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

Response of juvenile black rockfish (Sebastes schlegelii) to water temperature: Growth, antioxidant capacity, and metabolism - Xinting Mu; Qing Li; Zhiqiang Zhang; Xiaoqian Cheng; He Ma; Tomoaki Itayama; Rui Han; Yinghai Wu (Aquaculture International, 2026)

The PpERF3 promotes ethylene-induced anthocyanin biosynthesis in peach - Qingbing You; Jiaqi Mu; Qing Wang; Tingting Xiao; Mingming Chang; Yueping Liu (Plant Science, 2026)

A new strategy to reduce casein antigenicity: Investigating immune response, gut microbiota dysbiosis, and metabolic changes in allergic mice - Qi Sun; Peng Sun; Qing Zhao; Xiaomeng Wu; Fanhua Kong; Guangqing Mu (Food Chemistry, 2026)

Environmental filtering drives microbial niche shift from generalists to specialists during the aging of proglacial lakes - Xiaodong Li; Bingya Zhang; Qing Yang; Zhao Xue; Guangli Mu; Meiqi Huang; Qianggong Zhang; Jinrong Huang; Yingxin Zhao; Yindong Tong (Limnology and Oceanography, 2026)
Global warming is altering material cycles in cryospheric and aquatic ecosystems. Accelerated glacier retreat has spurred the formation of numerous proglacial lakes, providing ideal natural laboratories for studying early ecological succession. However, the mechanisms driving microbial succession as these lakes age, particularly shifts in niche strategies and community assembly, remain poorly understood. We investigated 12 proglacial lakes at distinct developmental stages on the central Qinghai‐Tibet Plateau, with formation dates ranging from before the 1980s to 2020. By integrating 16S/18S rRNA sequencing, molecular networks, and null models, we characterized microbial successional trajectories along this gradient. As lakes aged, α‐diversity decreased whereas β ‐diversity increased for both bacteria and eukaryotes, and this β ‐diversity shift was primarily attributable to species turnover. These changes coincided with systemic niche contraction and network simplification, leading to a significant decline in community stability. Notably, assembly processes differed between bacteria and eukaryotes. Bacterial communities shifted from stochasticity to homogeneous selection, whereas eukaryotic assembly was consistently governed by dispersal limitation. Functionally, bacteria transitioned from high‐cost stress‐response traits such as cold shock proteins to efficient nutrient biosynthesis including histidine and lysine. Together, these findings advance our understanding of divergent microbial succession and assembly mechanisms in proglacial lakes, providing critical insights into ecosystem development under climate‐driven glacier retreat.

Enhanced chlorine photolysis and 1H-benzotriazole degradation in water under the Far-UVC (UV222) irradiation - Jia-Jing Lyu; Qing Bai; Qian-Yuan Wu; Yu-Jia Nong; Mu-Da Han; Min-Yong Lee; Zhong-Quan Ren; Jiang-Lei Xiong; Wen-Long Wang (Journal of Environmental Chemical Engineering, 2026)

Substantial discrepancies across global fire emissions inventories: a systematic intercomparison - Jiyuan Yang; Hanyue Zheng; Peng Zhao; Johannes W. Kaiser; Qing Mu (Journal of Environmental Sciences, 2026)

Sustainable stabilisation of collapsible loess with quicklime-recycled GGBS mixtures - Bao-Lin Dai; Chao Zhou; Qing-Yi Mu; Jian-Bing Peng (Geomechanics for Energy and the Environment, 2026)

Data driven analysis on changing patterns of reactive nitrogen deposition in East and Southeast Asia - Jiani Tan; Yan Zhang; Xuejun Liu; Yun Fat LAM; Mohd Talib Latif; Kasemsan Manomaiphiboon; Joshua S. Fu; Maggie Chel Gee Ooi; Ling Huang; Yangjun Wang; Hui Chen; Kun Zhang; et al. (Atmospheric Environment, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

A Study of the Transportation and Evaporation of a Teacher’s Respiratory Droplet Aerosols in a Ventilated Classroom - Hongmei Liu; Mu Chen; Qing Zhang; Xiao Jiang; Xuedong Liu (Aerosol Science and Engineering, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Establishment of a Hybrid Snakehead Spleen Cell Line for Viral Studies - Xuanming Liu; Qing wang; Xiudong Guo; Yingying Li; Xubing Mo; Jiyuan Yin; Shucheng Zheng; Jian Zhao; Xidong Mu; Yingying Wang (Journal of Fish Diseases, 2026)
A spleen‐derived cell line was established from the spleen of hybrid snakehead (♀ Channa argus × ♂ Channa maculata ) (abbreviated as CAMsp ), a species of considerable economic importance in China's freshwater aquaculture, which is severely impacted by the hybrid snakehead rhabdovirus ( HSHRV ), largemouth bass ranavirus ( LMBV ), and infectious spleen and kidney necrosis virus ( ISKNV ). The establishment of a stable in vitro culture system is imperative for the effective isolation, identification, and study of fish viruses. CAMsp , generated through trypsin digestion, had successfully undergone over 80 passages since its initial culture. This cell line exhibited rapid proliferation in Leibovitz's‐15 medium (L‐15) supplemented with 10% fetal bovine serum at 28°C, achieving monolayer formation within 24 h at a passage ratio of 1:3. Chromosomal analysis of CAMsp at the 60th passage identified a chromosome count of 42; the chromosome number in hybrid snakehead somatic cells is 44, 45, or 46, suggesting chromosomal alterations. Inoculation of CAMsp monolayers with HSHRV , LMBV , and ISKNV resulted in characteristic cytopathic effects ( CPE ), including cell rounding, aggregation, and eventual detachment. Transmission electron microscopy ( TEM ) confirmed viral replication and revealed extensive cytopathological changes within the infected cells, demonstrating the susceptibility of the CAMsp cell line to all three viruses. Viral titers, determined by TCID 50 assay at 7 days post‐infection (dpi), reached 10 9.25 ± 10 0.36 TCID 50 / mL for LMBV , 10 6 · 15 ± 10 0.25 TCID 50 / mL for ISKNV , and 10 8 · 33 ± 10 0.12 TCID 50 / mL for HSHRV , indicating efficient viral propagation in this cell line. The CAMsp cell line serves as a valuable model for studying certain fish viruses, virus‐host interactions, and disease prevention strategies.

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Glacial melting enhances the influence of microbial cross-domain interactions on dissolved organic carbon dynamics across the high-altitude glacier-proglacial lake-river continuum - Yanan Zhou; Qing Yang; Hongyang Cui; Meiqi Huang; Zhao Xue; Guangli Mu; Feng Zhao; Liang Li; Xiaodong Li; Yindong Tong (Journal of Environmental Sciences, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Quinone structure regulates sulfide-driven reactive oxygen species generation for aquatic pollutant degradation - Han-Qing Zhao; Ruihan Yu; Jiayi Liu; Hong Cheng; Aqiang Ding; Daijun Zhang; Yang Mu; Peili Lu (Water Research, 2026)

Enrichment and cultivation of thermophilic Bathyarchaeia from oil reservoirs via systematic cultivation profiling - Qing-Ping He; Yi-Fan Liu; Bo-Wen Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Hypoxanthine accumulation caused by mutations of Bombyx mori xanthine dehydrogenase triggers female sterility - Wen-qing Lai; Zhan-peng Lu; Qiang Zhang; Zuo-min Shao; Han Gao; Xia Sun; Sheng Qin; Xue-yang Wang; Mu-wang Li (Insect Biochemistry and Molecular Biology, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Excavation instability with end restraint effect under high stress: insights from True-Triaxial simulation experiments - Ting Zhang; Si-Qiao Wang; Shi-Hong Wu; Mu-Qing Su; Jian-Zhi Zhang; Yong Niu (Bulletin of Engineering Geology and the Environment, 2026)

Defective bimetallic oxide Ce0.6Zr0.4O2 for simultaneous electrochemical detection and adsorptive removal of heavy metal ions - Dahui An; Junhua Zheng; Qing Wang; Mubai Liao; Shuchen Mu; Long Chen (Journal of Environmental Chemical Engineering, 2025)

Enzyme activity-enhanced MIL101(Fe) loaded PdSn Nanoenzymes enable ultrasensitive detection of oxytetracycline in foods - Yuanpei Pan; Zhaode Mu; Min Qing; Yijie Wu; Meili Deng; Lijuan Bai (Food Chemistry, 2025)

Discontinuation of glacial meltwater input reshapes the diversity and stability of eukaryotic planktonic microbial communities in glacial lakes - Xiaodong Li; Qianggong Zhang; Peng Zhang; Qing Yang; Zijian Lu; Yanan Zhou; Meiqi Huang; Guangli Mu; Zhao Xue; Linyuan Lu; Yindong Tong (Environmental Research, 2025)

Morphology of root systems and tensile properties of individual roots across various soil types and layer thicknesses induced by bedrock weathering - Bin-bin Guo; Qing-yi Mu; Yan-jun Shen; Anthony Kwan Leung; Jian-bing Peng (CATENA, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Effects of phenological uniformity on prediction accuracy of wheat yield and biomass - Yandong Yang; Qing Li; Qinwen Lin; Huimin Wang; Yi Shi; Gengchen Wu; Yue Mu; Dong Jiang; Seishi Ninomiya (Field Crops Research, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

Analysis and optimization of a quasi-zero-stiffness vibration isolator based on partially rigidized compliant mechanisms - Zhi-Qiang Zhang; Mu-Qing Niu; Li-Qun Chen (Engineering Structures, 2025)

Comprehensive analysis of greenhouse gases emissions and microbial dynamics in glacier-fed lakes across various ablation stages - Shuang Liu; Fuyuan Mai; Meiqi Huang; Qing Yang; Xiaodong Li; Guangli Mu; Bingya Zhang; Linyuan Lu; Yu Pang; Ding He; Qianggong Zhang; Yiwen Liu; et al. (Water Research, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

Water retention curves of a deformable lean clay under various stress ratios: Emphasizing the pore shape effects - Qing-yi Mu; Tian-qi Song; Chao Zhou; Jian-bing Peng (Computers and Geotechnics, 2025)

The strong electron coupling of MnCo2S4/ZnCdS Ohmic junction enhances photocatalytic hydrogen evolution - Qing Chen; Kai Wang; Dandan Mu; Zhiliang Jin (Chemical Engineering Journal, 2025)

The Systematic Study on the Effects of Adding Bile Acids and Zinc to Laying Hens’ Diets: From Production Performance to Egg Quality, Trace Element Content, and Intestinal Microorganisms - Shou Kang Cao; Yi Fan Li; Han Chen; Yu Qing Mu; Xue Zhuang Wu (Biological Trace Element Research, 2025)

Epithelial cells facilitate tissue fibrosis through early growth response-1 overexpression in IgG4-related disease - Ruijie Sun; Qinhuan Luo; Mu Wang; Linyi Peng; Wei Wei; Yanmei Li; Jiaxin Zhou; Yuxue Nie; Jingna Li; Qing Zhong; Yunyun Fei; Mengtao Li; et al. (Science Bulletin, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Applying stacked machine learning models to guide electrochemical oxidation of antibiotics: Key parameter identification and process optimization insights - Shichang Jia; Min Deng; Yue Mu; Jiahang Li; Xiaosong Tian; Qing Xie; Jinzhong Zhang (Journal of Environmental Management, 2025)

Synergistic microstructure regulation of coal tar pitch based‑carbon by pre-oxidation and iodine treatment for its high-plateau-capacity sodium storage - Yuli Wei; Qing Wang; Qing Liu; Rongzhe Wang; Shaohua Luo; Lixiong Qian; Yahui Zhang; Pengqing Hou; Shengxue Yan; Xin Liu; Jing Guo; Wenning Mu (Chemical Engineering Journal, 2025)

Evaporation characteristics and photothermal conversion in core-shell Fe3O4@TiO2 nanostructured fluids - Xinghe Dai; Weifeng Zhang; Juan Duan; Shan Qing; Yiyun Mu; Mingci Hu (Journal of Water Process Engineering, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Methane cycling in typical emerging proglacial lakes on the Tibetan Plateau: Insights into the metabolic mechanisms mediated by microorganisms - Meiqi Huang; Guangli Mu; Fuyuan Mai; Yanan Zhou; Xiaodong Li; Qing Yang; Bo Shao; Jiaqi Wang; Yindong Tong (Water Research, 2025)

Characteristics of nutrients and microbial communities in proglacial lakes on the Tibetan Plateau and their potential linkages associated with mercury - Guangli Mu; Meiqi Huang; Zhengyu Wu; Hongyang Cui; Qing Yang; Xiaodong Li; Xiaoyu Cui; Yindong Tong (Journal of Hazardous Materials, 2025)

The effects of the 2D aligned fibers on the fracture properties of steel fiber reinforced cementitious composite slab: Simulation and experimental validation - Kelai Yu; Yu Hu; Ru Mu; Peng Xing; Nan Zhao; Longbang Qing (Engineering Structures, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

Recommendations on benchmarks for the DeNitrification–DeComposition model application in China: Insights from literature analysis - Nanchi Shen; Jiani Tan; Qing Mu; Ling Huang; Wenbo Xue; Yangjun Wang; Maggie Chel Gee Ooi; Mohd Talib Latif; Gang Yan; Lam Yun Fat Nicky; Li Li (Environmental Modelling & Software, 2025)

Enhanced response for triethylamine detection by NiCo2O4-In2O3 composites gas sensor - Qing Yue; Tao Liu; Yang Mu; Xingtai Chen; Xi-Tao Yin (Chemical Engineering Journal, 2025)

Comparative lipidome revealed an increase of unsaturated lipids in Bifidobacterium animalis subsp. lactis 420 by linoleic acid supplementation - Qing Liao; Shuyan Wu; Ziyi Tang; Xi Yang; Ming Huang; Xing Weng; Xia Yu; Xiaoyuan Wang; Mu Zhang; Meijuan Xu; Xiaoqing Hu (Systems Microbiology and Biomanufacturing, 2025)

A novel and flexible way to derive water quality criteria for copper - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Science of The Total Environment, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Extraction of copper from chalcopyrite by clean and efficient chlorination process to prepare Cu-Fe bimetallic oxide for Li-ion batteries: A facile method in view of sustainable engineering - Xiaolong Bi; Wenning Mu; Anlu Wei; Mengjie Han; Xuefei Lei; Qing Wang; Shaohua Luo (Chemical Engineering Journal, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Associations between co-exposure to multiple heavy metals and age-related macular degeneration: A cross-sectional study - Mu-hong Wei; Ju-xiao Li; Jing Mi; Qing Wang; Feng Xu; Che Xu (Journal of Trace Elements in Medicine and Biology, 2025)

A novel aptasensor integrating the DNA rolling nanomachine and Tb/COF/KB as dual signal amplifiers for kanamycin detection in foods - Yujie Chen; Zhaode Mu; Jianli Zuo; Min Qing; Jing Zhou; Lijuan Bai (Food Chemistry, 2025)

Optimizing β-Lactoglobulin antigenicity through single enzyme hydrolysis: Exploring structural changes and effects on linear epitopes - Peng Sun; Xiaomeng Wu; Qi Sun; Qing Zhao; Guangqing Mu; Fanhua Kong (Food Chemistry, 2025)

Dimeric PD-L1 specific affibody grafted Fe-based nanosheets for tumor-targeting dual-mode magnet resonance imaging and enhancement of Photothermal-Immunotherapy - Xinyu Zhang; Hui Liu; Chenyu Wang; Yuan Gao; Shiqi Zhao; Mengyao Mu; Ke Ren; Yufang Gong; Qing Fan; Xiao Sun (Chemical Engineering Journal, 2025)

Real-time Bayesian axle load estimation and structural identification of railway bridges under train loads based on strain monitoring - Hou-Zuo Guo; Ka-Veng Yuen; He-Qing Mu (Engineering Structures, 2025)

A compliant helical structure to amplify inertia for nonlinear vibration absorption - Jun-Jie Huang; Mu-Qing Niu; Yimin Fan; Li-Qun Chen (Engineering Structures, 2025)

Overcoming radiation-induced PD-L1 upregulation by novel gadolinium-palladium nanoplatforms for enhanced tumor radio-immunotherapy - Kai Guo; Hui Liu; Mengmeng Zhang; Nengyi Ni; Mengyao Mu; Ke Ren; Jiahui Chen; Qing Fan; Xueli Xu; Xiao Sun; Ximing Wang (Chemical Engineering Journal, 2025)

Regulation mechanisms of allergenic epitope sites in casein by microbial and plant-derived proteases - Qi Sun; Guangqing Mu; Peng Sun; Qing Zhao; Xiaomeng Wu; Fanhua Kong (Food Bioscience, 2024)

Derivation of marine water quality criteria for copper based on artificial neural network model - Yang Li; Di Mu; Hong-Qing Wu; Xian-Hua Liu; Jun Sun; Zhi-Yong Ji (Environmental Pollution, 2024)

Protonated polyethyleneimine enables synchronous crosslinking of polyimide nanofiltration membranes for dye desalination - Qing Fang; Sudan Lan; Xiuxiu Mu; Yanping Zhang; Ya Li; Yajuan Wang; Lihui Yao; Yuyun Chen; Dan Qiu; Linghui Wang (Desalination, 2024)

A multifunctional nanoplatform capable of dual action on tumor PD-L1 for enhanced cancer theranostics - Mengyao Mu; Mengmeng Zhang; Yufang Gong; Kai Guo; Hui Liu; Zeran Zhang; Tongxin Jiang; Houren Zhou; Qing Fan; Dianlong Jia; Yuqin Li; Xiao Sun (Chemical Engineering Journal, 2024)

Isolation and Functional Analysis of Na+/H+ Antiporter Gene (LcNHX1) from Leymus chinensis - Chuanbo Sun; Chuang Zhang; Yuejia Yin; Ying Wang; Shujing Mu; Qing Liu; Ziyu Wang; Yang Liu; Chunxiao Zhang; Xiangguo Liu; Yan Zhang; Jia Guo (Plant Molecular Biology Reporter, 2024)

Enhancement and Preservation of Tufa Geosites in the Baishuitai Region, Yunnan Province, Southwest China - Hong-Xu Mu; Qing-Wei Song; Gui-Hua Wu; Long-Xin Xu (Geoheritage, 2024)

Downward shortwave radiation modeling over rugged terrain with clouds - Guangjian Yan; Chunqiang Zhao; Qing Chu; Xihan Mu; Yingji Zhou; Yanan Liu; Xuejun Wang; Donghui Xie (Remote Sensing of Environment, 2024)

Bi-allelic missense variants in MEI4 cause preimplantation embryonic arrest and female infertility - Zhiqi Pan; Weijie Wang; Ling Wu; Zhongyuan Yao; Wenjing Wang; Yao Chen; Hao Gu; Jie Dong; Jian Mu; Zhihua Zhang; Jing Fu; Qiaoli Li; et al. (Human Genetics, 2024)

Effect of composite cultivation on the meat quality of crucian carp (Carassius auratus) - Yin Zhang; Yunlong Mu; Linguo Wang; Qing Zeng; Pengcheng Zhang; Haichuan Peng; Qiuyue Chen; Jianlin Jia; Zhongli Pan; Qing Li (Aquaculture International, 2024)

Evaluation of the collapse susceptibility of loess using machine learning - Qing-yi Mu; Tian-qi Song; Zhao Lu; Te Xiao; Li-min Zhang (Transportation Geotechnics, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

Spatiotemporal joint analysis of PM2.5 and Ozone in California with INLA approach - Jianan Pan; Kunyang He; Kai Wang; Qing Mu; Chengxiu Ling (Journal of Environmental Management, 2024)

A gas-mechanical-damage coupling model based on the TLF-SPH method and its application to gas seepage in fractured coal - Dianrui Mu; Qing Ma; Ke Zhang; Jiyuan Zhao (Computers and Geotechnics, 2024)

Exploring lipid digestion discrepancies between preterm formula and human milk: Insights from in vitro gastrointestinal digestion and the impact of added milk fat - Ning Wang; Sen Yang; Guang-Qing Mu; Fang Qian; Xue-Mei Zhu (Food Research International, 2024)

Fermented bile acids improved growth performance and intestinal health by altering metabolic profiles and intestinal microbiome in Micropterus salmoides - Qing Guo; Wenwen Liu; Lu Zhao; Yiming Sui; Houfa Zhao; Yining Liu; Cuimin Mu; Xuepeng Wang (Fish & Shellfish Immunology, 2024)

Perfect cooperative pest control via nano-pesticide and natural predator: High predation selectivity and negligible toxicity toward predatory stinkbug - Shangyuan Wu; Qinhong Jiang; Zhilin Xia; Zhirong Sun; Qing Mu; Chunyang Huang; Fan Song; Meizhen Yin; Jie Shen; Hu Li; Shuo Yan (Chemosphere, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

Assessment of the sensitivity of model responses to urban emission changes in support of emission reduction strategies - Bertrand Bessagnet; Kees Cuvelier; Alexander de Meij; Alexandra Monteiro; Enrico Pisoni; Philippe Thunis; Angelos Violaris; Jonilda Kushta; Bruce R. Denby; Qing Mu; Eivind G. Wærsted; Marta G. Vivanco; et al. (Air Quality, Atmosphere & Health, 2024)
The sensitivity of air quality model responses to modifications in input data (e.g. emissions, meteorology and boundary conditions) or model configurations is recognized as an important issue for air quality modelling applications in support of air quality plans. In the framework of FAIRMODE (Forum of Air Quality Modelling in Europe, https://fairmode.jrc.ec.europa.eu/ ) a dedicated air quality modelling exercise has been designed to address this issue. The main goal was to evaluate the magnitude and variability of air quality model responses when studying emission scenarios/projections by assessing the changes of model output in response to emission changes. This work is based on several air quality models that are used to support model users and developers, and, consequently, policy makers. We present the FAIRMODE exercise and the participating models, and provide an analysis of the variability of O 3 and PM concentrations due to emission reduction scenarios. The key novel feature, in comparison with other exercises, is that emission reduction strategies in the present work are applied and evaluated at urban scale over a large number of cities using new indicators such as the absolute potential, the relative potential and the absolute potency. The results show that there is a larger variability of concentration changes between models, when the emission reduction scenarios are applied, than for their respective baseline absolute concentrations. For ozone, the variability between models of absolute baseline concentrations is below 10%, while the variability of concentration changes (when emissions are similarly perturbed) exceeds, in some instances 100% or higher during episodes. Combined emission reductions are usually more efficient than the sum of single precursor emission reductions both for O 3 and PM. In particular for ozone, model responses, in terms of linearity and additivity, show a clear impact of non-linear chemistry processes. This analysis gives an insight into the impact of model’ sensitivity to emission reductions that may be considered when designing air quality plans and paves the way of more in-depth analysis to disentangle the role of emissions from model formulation for present and future air quality assessments.

Development of an alternative low-cost culture medium for a new isolated high-production DHA strain using kitchen wastewater - Qing Wang; Wenbiao Jin; Yujia Qin; Xu Zhou; Wei Han; Shuhong Gao; Xuan Li; Mu. Naushad; Guangming Jiang; Huan Liu (Process Safety and Environmental Protection, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

Aggregation-induced enhancement of pyrene-based metal-organic framework as a new electrochemiluminescence emitter for ultrasensitive detection of sulfadimethoxine - Junjie Liu; Zhaode Mu; Jing Zhou; Min Qing; Lijuan Bai (Food Chemistry, 2024)

Evaluation of long-term spatio-temporal characteristics of water and nitrogen in the vadose zone and potential threats to groundwater under different irrigation strategies - Jiatun Xu; Qing Mu; Shikun Sun; Nan Yang; Xiongbiao Peng; Yufeng Zou; Shaoyuan Feng; Huanjie Cai (Journal of Cleaner Production, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

High-performance inkjet-printed inverted QD-LEDs based on cross-linkable electron regulation layers - Liming Xie; Qing Li; Yuan-Qiu-Qiang Yi; Gengrui Qiu; Omolola Esther Fayemi; Xinju Mu; Zhongsheng Ma; Pengyu Tang; Yang Liu; Wenming Su; Wei Lei; Zheng Cui (Chemical Engineering Journal, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Lactic acid bacteria with probiotic characteristics in fermented dairy products reduce cow milk allergy - Zi-Hao Guo; Qi Wang; Jing-Hong Zhao; Yun-Peng Xu; Guang-Qing Mu; Xue-Mei Zhu (Food Bioscience, 2023)

Refining health risk assessment of arsenic in wild edible boletus from typical high geochemical background areas: The role of As species, bioavailability, and enterotoxicity - Mengying Li; Zheng Chen; Qing Xiong; Yunzhen Mu; Yumei Xie; Mengyan Zhang; Lena Q. Ma; Ping Xiang (Environmental Pollution, 2023)

Endoplasmic reticulum stress: a vital process and potential therapeutic target in chronic obstructive pulmonary disease - Hao Peng; Qing Zhou; Jing Liu; Yi Wang; Ketao Mu; Lei Zhang (Inflammation Research, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Engineered metal coverage of anode catalyst layer enhancing cell reversal tolerance for proton exchange membrane fuel cells - Zheng Li; Haodong Huang; Yameng Wang; Yongbiao Mu; Yuting Jiang; Qing Zhang; Tianshou Zhao; Lin Zeng (Chemical Engineering Journal, 2023)

Short-chain fatty acids (SCFAs) as potential resuscitation factors that promote the isolation and culture of uncultured bacteria in marine sediments - Chun-Shui Sun; Liu-Yan Zhou; Qi-Yun Liang; Xiao-Man Wang; Yi-Xuan Lei; Zhen-Xing Xu; Feng-Qing Wang; Guan-Jun Chen; Zong-Jun Du; Da-Shuai Mu (Marine Life Science & Technology, 2023)
Many marine bacteria are difficult to culture because they are dormant, rare or found in low-abundances. Enrichment culturing has been widely tested as an important strategy to isolate rare or dormant microbes. However, many more mechanisms remain uncertain. Here, based on 16S rRNA gene high-throughput sequencing and metabolomics technology, it was found that the short-chain fatty acids (SCFAs) in metabolites were significantly correlated with uncultured bacterial groups during enrichment cultures. A pure culture analysis showed that the addition of SCFAs to media also resulted in high efficiency for the isolation of uncultured strains from marine sediments. As a result, 238 strains belonging to 10 phyla, 26 families and 82 species were successfully isolated. Some uncultured rare taxa within Chlorobi and Kiritimatiellaeota were successfully cultured . Amongst the newly isolated uncultured microbes, most genomes, e.g. bacteria, possess SCFA oxidative degradation genes, and these features might aid these microbes in better adapting to the culture media. A further resuscitation analysis of a viable but non-culturable (VBNC) Marinilabiliales strain verified that the addition of SCFAs could break the dormancy of Marinilabiliales in 5 days, and the growth curve test showed that the SCFAs could shorten the lag phase and increase the growth rate. Overall, this study provides new insights into SCFAs, which were first studied as resuscitation factors in uncultured marine bacteria. Thus, this study can help improve the utilisation and excavation of marine microbial resources, especially for the most-wanted or key players.

An enzymatic activity regulation-based clusterzyme sensor array for high-throughput identification of heavy metal ions - Yueyuan Li; Zhaode Mu; Yonghua Yuan; Jing Zhou; Lijuan Bai; Min Qing (Journal of Hazardous Materials, 2023)

Underlying mechanisms for natural organic matters mediated aerobic ciprofloxacin transformation by sulfide - Han-Qing Zhao; Peili Lu; Fei Chen; Hongcheng Bai; Chen-Xuan Li; Guan-Nan Zhou; Jing Wang; Lilan Zhang; Yang Mu (Journal of Environmental Chemical Engineering, 2023)

Influence on physical properties and digestive characters of fermented coconut milk with different loading proportion of skimmed coconut drink using Lactiplantibacillus plantarum MWLp-4 from human milk mixing with commercial bacteria - Qing Zhao; Zining Wang; Zengxin Yu; Zhongyang Gao; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Effects of solar radiation and fine roots on suction of Amorpha fruticose-vegetated soil - Han-qing Guo; Xiao-qing Chen; Dong-ri Song; Qing-yi Mu; Hamed Sadeghi; Hao Jiang; Ming Lv (Journal of Mountain Science, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

ROS filter coating scaffold protects 3D mesenchymal stem cell spheroids for dual-phase treatment of spinal cord injury - Jian Cao; Jiahe Wu; Jiafu Mu; Lingmin Lin; Xunqi Zhang; Tianchen Huang; Teng Ma; Manning Zhu; Xiaoyang Dai; Xuhua Wang; Shiqing Feng; Jian-Qing Gao (Chemical Engineering Journal, 2023)

Flavobacterium potami sp. nov., a multi-metal resistance genes harbouring bacterium isolated from shallow river silt - Shucheng Li; Sidi Mao; Weidong Mu; Bai Guo; Chen Li; Qing Zhu; Xiaoxiao Hou; Yanfang Zhao; Shuzhen Wei; Hongliang Liu; Aiju Liu (Antonie van Leeuwenhoek, 2023)

Considering spatio-temporal dynamics of soil water with evapotranspiration partitioning helps to clarify water utilization characteristics of summer maize under deficit irrigation - Jiatun Xu; Qing Mu; Yibo Ding; Shikun Sun; Yufeng Zou; Lianyu Yu; Pengyan Zhang; Nan Yang; Wei Guo; Huanjie Cai (Journal of Hydrology, 2023)

Single atom Co-anchored nitrogen‑doped graphene for peroxymonosulfate activation with high selectivity of singlet oxygen generation - Han-Qing Zhao; Jun-Sheng Song; Peili Lu; Yang Mu (Chemical Engineering Journal, 2023)

Neural Mechanism Underlying Task-Specific Enhancement of Motor Learning by Concurrent Transcranial Direct Current Stimulation - Ying Wang; Jixian Wang; Qing-Fang Zhang; Ke-Wei Xiao; Liang Wang; Qing-Ping Yu; Qing Xie; Mu-Ming Poo; Yunqing Wen (Neuroscience Bulletin, 2023)

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

Xinfangfangia pollutisoli sp. nov., Isolated from Clopyralid-Contaminated Soil - Yang Mu; Jia-Yi Peng; Hui-Ping Wang; Yue Song; Hong-Mei Wang; Qing Chen; Kai Chen (Current Microbiology, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

First report of Pseudocercospora coprosmae causing leaf spot on Scaevola taccada in China - Min Li; Zhaoyin Gao; Xiqiang Song; Qing Chen; Deqiang Gong; Junxia Mu; Meijiao Hu (Journal of Plant Pathology, 2022)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Numerical Study on an Innovative Shaped Charge Approach of Rock Blasting and the Timing Sequence Effect in Microsecond Magnitude - Yao Yin; Qing Sun; Baoping Zou; Qingyi Mu (Rock Mechanics and Rock Engineering, 2021)

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

Altered dynamics of functional connectivity density associated with early and advanced stages of motor training in tennis and table tennis athletes - Qing Gao; Yue Huang; Yu Xiang; Chengbo Yang; Mu Zhang; Jingpu Guo; Hu Wang; Jiali Yu; Qian Cui; Huafu Chen (Brain Imaging and Behavior, 2021)

Correction to: A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

Dissection and validation of a QTL cluster linked to Rht-B1 locus controlling grain weight in common wheat (Triticum aestivum L.) using near-isogenic lines - Panfeng Guan; Xueyi Shen; Qing Mu; Yongfa Wang; Xiaobo Wang; Yongming Chen; Yue Zhao; Xiyong Chen; Aiju Zhao; Weiwei Mao; Yiwen Guo; Mingming Xin; et al. (Theoretical and Applied Genetics, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Noncoding RNAs: functional regulatory factors in tomato fruit ripening - Lili Ma; Jianlou Mu; Donald Grierson; Yunxiang Wang; Lipu Gao; Xiaoyan Zhao; Benzhong Zhu; Yunbo Luo; Kai Shi; Qing Wang; Jinhua Zuo (Theoretical and Applied Genetics, 2020)

Association between occupational exposure to trichloroethylene and serum levels of microRNAs: a cross-sectional molecular epidemiology study in China - Kyoung-Mu Lee; Bryan A. Bassig; Luoping Zhang; Roel C. Vermeulen; Wei Hu; Jason Y. Y. Wong; Chuangyi Qiu; Cuiju Wen; Yongshun Huang; Mark P. Purdue; Bu-Tian Ji; Laiyu Li; et al. (International Archives of Occupational and Environmental Health, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

A structure–activity relationship study of phenyl sesquiterpenoids on efflux inhibition against Staphylococcus aureus - Zhong-Lin Sun; Tao Liu; Simon Gibbons; Qing Mu (Medicinal Chemistry Research, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

Effects of water content on the shear behavior and critical state of glacial till in Tianmo Gully of Tibet, China - Gordon G. D. Zhou; Lei-lei Chen; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

Compression characteristics of saturated re-compacted glacial tills in Tianmo Gully of Tibet, China - Lei-lei Chen; Gordon G. D. Zhou; Qing-yi Mu; Kahlil Fredrick E. Cui; Dong-ri Song (Journal of Mountain Science, 2019)

TLC-bioautography directed isolation of antibacterial compounds from active fractionation of Ferula ferulioides - Zhong-Lin Sun; Tao Liu; Shuang-Ying Wang; Xiao-Yue Ji; Qing Mu (Natural Product Research, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Pedobacter pollutisoli sp. nov., Isolated from Tetrabromobisphenol A-Contaminated Soil - Yang Mu; Zhuang Ke; Chen-Xi Feng; Xiao-Wei Wang; Xiao-Wen Wang; Hong-Mei Wang; Qing Chen; Jian He (Current Microbiology, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Efficiency of sequential UV/H2O2 and biofilm process for the treatment of secondary effluent - Peng-Fei Yan; Shoujun Yuan; Wei Wang; Zhen-Hu Hu; Yang Mu; Han-Qing Yu (Environmental Science and Pollution Research, 2019)

Isolation and functional characterization of the SpCBF1 gene from Solanum pinnatisectum - Wenjiao Zhu; Ke Shi; Ruimin Tang; Xiaoying Mu; Jinghui Cai; Min Chen; Xiong You; Qing Yang (Physiology and Molecular Biology of Plants, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Synergistic effects of temperature and humidity on the symptoms of COPD patients - Zhe Mu; Pei-Li Chen; Fu-Hai Geng; Lei Ren; Wen-Chao Gu; Jia-Yun Ma; Li Peng; Qing-Yun Li (International Journal of Biometeorology, 2017)

Artificial Inoculation Method of Pokkah Boeng Disease of Sugarcane and Screening of Resistant Germplasm Resources in Subtropical China - Ze-Ping Wang; Hai-Jun Sun; Qiang Guo; Shi-Qiang Xu; Ji-Hua Wang; Shan-Hai Lin; Mu-Qing Zhang (Sugar Tech, 2017)

Screening, purification, and characterization of a novel organic solvent-tolerant esterase, Lip2, from Monascus purpureus strain M7 - Li-Jing Kang; Zi-Tong Meng; Chen Hu; Yan Zhang; Hai-Lun Guo; Qing Li; Mu Li (Extremophiles, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

Transcription response of three putative trehalase genes to hormonal stimulation in the Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Ji-Feng Shi; Qiang-Kun Sun; Li-Li Mu; Wen-Chao Guo; Guo-Qing Li (Applied Entomology and Zoology, 2017)

Ecological effects of rice-duck integrated farming on soil fertility and weed and pest control - Qing Teng; Xue-Feng Hu; Chang Cheng; Zhiqing Luo; Fan Luo; Yong Xue; Yijun Jiang; Zhen Mu; Liming Liu; Minyong Yang (Journal of Soils and Sediments, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

Rational Improvement of Peptide Affinity to Human Pregnancy-Related Serine Protease HtrA3 PDZ Domain by Introducing a Halogen Bond to the Domain–Peptide Complex Interface - Hong Liu; Shuo-Fen Dou; Xue Zhang; Yan Wang; Qing-Li Wen; Ya-Nan Mu (International Journal of Peptide Research and Therapeutics, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

The Tau-Induced Reduction of mRNA Levels of Kv Channels in Human Neuroblastoma SK-N-SH Cells - Xi-Mu Hu; Xiao-Qing Li; Xian-Tao Li (Journal of Molecular Neuroscience, 2016)

Cloning and expression of a wild eggplant cytochrome P450 gene, StoCYP77A2, involved in plant resistance to Verticillium dahliae - Liu Yang; Ce Shi; Xiaoying Mu; Chao Liu; Ke Shi; Wenjiao Zhu; Qing Yang (Plant Biotechnology Reports, 2015)

Occurrence of sulfonamide-, tetracycline-, plasmid-mediated quinolone- and macrolide-resistance genes in livestock feedlots in Northern China - Quanhua Mu; Jin Li; Yingxue Sun; Daqing Mao; Qing Wang; Yi Luo (Environmental Science and Pollution Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Breeding of cabbage (Brassica oleracea L. var. capitata) with fusarium wilt resistance based on microspore culture and marker-assisted selection - Hong-hao Lv; Qing-biao Wang; Li-mei Yang; Zhi-yuan Fang; Yu-mei Liu; Mu Zhuang; Yang-yong Zhang; Yu-hong Yang; Bing-yan Xie; Xiao-wu Wang (Euphytica, 2014)

The role of mast cells in ischemia and reperfusion injury - Mu-qing Yang; Yuan-yuan Ma; Jing Ding; Ji-yu Li (Inflammation Research, 2014)

Prognostic significance of TBX2 expression in non-small cell lung cancer - Bo Hu; Hai-Ping Mu; Yu-Qing Zhang; Chong-Yi Su; Jian-Tao Song; Chong Meng; Dong-Xing Liu (Journal of Molecular Histology, 2014)

Molecular identification and interaction assay of the gene (OsUbc13) encoding a ubiquitin-conjugating enzyme in rice - Ya Wang; Meng-yun Xu; Jian-ping Liu; Mu-gui Wang; Hai-qing Yin; Ju-min Tu (Journal of Zhejiang University-SCIENCE B, 2014)

Inhibiting mast cell degranulation by HO-1 affects dendritic cell maturation in vitro - Yuan-yuan Ma; Mu-qing Yang; Chun-feng Wang; Jing Ding; Ji-yu Li (Inflammation Research, 2014)

Seismic attenuation relationship with homogeneous and heterogeneous prediction-error variance models - He-Qing Mu; Rong-Rong Xu; Ka-Veng Yuen (Earthquake Engineering and Engineering Vibration, 2014)

Cytokine Profile of a Self-Healing Fonsecaea pedrosoi Infection in Murine Model - Hong Wang; Weidong Mu; Qing Ja; Miao Zhang; Ruie Chen; Guixia Lv; Yongnian Shen; Weida Liu (Cell Biochemistry and Biophysics, 2013)

Genetic diversity of two Tibetan macaque (Macaca thibetana) populations from Guizhou and Yunnan in China based on mitochondrial DNA D-loop sequences - Li-Jing Zhong; Ming-Wang Zhang; Yong-Fang Yao; Qing-Yong Ni; Jun Mu; Chong-Qing Li; Huai-Liang Xu (Genes & Genomics, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of humus on the environmental activity of mineral-bound Hg: influence on Hg plant uptake - Aijun Yao; Rongliang Qiu; Changle Qing; Shusen Mu; Eric J. Reardon (Journal of Soils and Sediments, 2011)

Immune response to fused core protein of hepatitis C virus and truncated tetanus toxin peptides in mice - Xing-bin Hu; Qiao-hong Yue; Hai-feng Ouyang; Yao-zhen Chen; Xue-qing Xu; Wen Yin; San-hua Wei; Xian-qing Zhang; Shi-jie Mu (Archives of Virology, 2010)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Molecular cloning and characterisation of a non-TIR-NBS-LRR type disease resistance gene analogue from sugarcane - Q. You-Xiong; L. Jian-Wei; Z. Ji-Sen; R. Miao-Hong; X. Li-Ping; Z. Mu-Qing (Sugar Tech, 2008)

Plants interactions between Suaeda salsa individuals are mediated by salinity stress - Hao Zhang; Jian-Na Li; Gen-Xuan Wang; Xin-Feng Dai; Mu-Qing Qiu; Ke-Feng Zheng (Acta Physiologiae Plantarum, 2007)

One-carbon metabolism gene polymorphisms and risk of non-Hodgkin lymphoma in Australia - Kyoung-Mu Lee; Qing Lan; Anne Kricker; Mark P. Purdue; Andrew E. Grulich; Claire M. Vajdic; Jennifer Turner; Denise Whitby; Daehee Kang; Stephen Chanock; Nathaniel Rothman; Bruce K. Armstrong (Human Genetics, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Effect of sensitivity to abscisic acid on scaling relationships for biomass production rates and body size in Arabidopsis thaliana - Hao Zhang; Gen-Xuan Wang; Zhu-Xia Shen; Xing-Zheng Zhao; Mu-Qing Qiu (Acta Physiologiae Plantarum, 2006)

Impact of elevated CO2 concentration under three soil water levels on growth of Cinnamomum camphora - Xing-zheng Zhao; Gen-xuan Wang; Zhu-xia Shen; Hao Zhang; Mu-qing Qiu (Journal of Zhejiang University-SCIENCE B, 2006)

High-yield conversion of (R)-2-octanol from the corresponding racemate by stereoinversion using Candida rugosa - Yao Nie; Yan Xu; Xiao Qing Mu; Yan Tang; Juan Jiang; Zhi Hao Sun (Biotechnology Letters, 2005)

Molecular marker application in sugarcane - Mu-Qing Zhang; Xue-Fang Zheng; Ai-Li Yu; Jing-Sheng Xu; Hui Zhou (Sugar Tech, 2004)

Mitochondrial DNA sequence polymorphisms of five ethnic populations from northern China - Qing-Peng Kong; Yong-Gang Yao; Mu Liu; Shu-Ping Shen; Cai Chen; Chun-Ling Zhu; Malliya Gounder Palanichamy; Ya-Ping Zhang (Human Genetics, 2003)

Protoplast culture and paclitaxel production by Taxus yunnanensis - Jian-Ping Luo; Qing Mu; Yue-Hua Gu (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)